Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Step-by-step explanation:
=3(2+c)-2(c-5)
=6+3c-2c+5c
=6+6c
=6(1+c)
hope it helps.
well, first you need to expand the brackets.
so, 3 x 2=6, 3 x c=3c
and, -2 x c= -2c, -2 x -5= 10 as a negative times a negative is a positive.
you should have this;
6+3c-2c+10
to simplify, do 3c-2c=c
6+10=16
16+c
(I think)
so, 3 x 2=6, 3 x c=3c
and, -2 x c= -2c, -2 x -5= 10 as a negative times a negative is a positive.
you should have this;
6+3c-2c+10
to simplify, do 3c-2c=c
6+10=16
16+c
(I think)
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.